Biophysical Analysis to Assess the Interaction of CRAC and CARC Motif Peptides of Alpha Hemolysin of Escherichia coli with Membranes - Cané, Lucía (2023)
Alpha hemolysin of Escherichia coli (HlyA) is a pore-forming protein, which is a prototype of the “Repeat in Toxins” (RTX) family. It was demonstrated that HlyA-cholesterol interaction facilitates the insertion of the toxin into membranes. Putative cholesterol-binding sites, called cholesterol recognition/amino acid consensus (CRAC), and CARC (analogous to CRAC but with the opposite orientation) were identified in the HlyA sequence. In this context, two peptides were synthesized, one derived from a CARC site from the insertion domain of the toxin (residues 341-353) (PEP 1) and the other one from a CRAC site from the domain between the acylated lysines (residues 639-644) (PEP 2), to study their role in the interaction of HlyA with membranes. The interaction of peptides with membranes of different lipid compositions (pure POPC and POPC/Cho of 4:1 and 2:1 molar ratios) was analyzed by surface plasmon resonance and molecular dynamics simulations. Results demonstrate that both peptides interact preferentially with Cho-containing membranes, although PEP 2 presents a lower KD than PEP 1. Molecular dynamics simulation results indicate that the insertion and interaction of PEP 2 with Cho-containing membranes are more prominent than those caused by PEP 1. The hemolytic activity of HlyA in the presence of peptides indicates that PEP 2 was the only one that inhibits HlyA activity, interfering in the binding between the toxin and cholesterol.